Effect of Pomegranate Seed Oil against Hepatotoxicity- Induced by Sodium Fluoride in Adult Female Rats (Part II).: براء نجم العقيلي وإيلاف حسين علي - Al-Okaily, Baraa Najim; Ali , Ellaf Hussian (The Iraqi Journal of Veterinary Medicine, 2019)
This experiment was designed to evaluate the hepatoprotective effects of pomegranate seed oil against toxicity- induced by sodium fluoride and in normal rats. Twenty adult female Wistar rats were divided into four equal group and treated daily for 40 days as follows: Group C administered tap water and served as control , group T1 : received sodium fluoride 120ppm in drinking tap water, group T2: received both sodium fluoride 120ppm in drinking water and administered orally pometone (pomegranate seed oil) 30mg/kg B.W. and group T3 : administered pomegranate seed oil as in group T2 orally. Fasting blood samples were collected at 0, 20 and 40 days to estimation of some biochemical parameters and oxidative stress biomarkers . In addition, sections from liver were taken at the end of the experiment for histopathological study. The results revealed that SF (group T1) caused a significant increase in serum aminotransferases (serum alanine aminotransferase and aspartate aminotransferase) activities, total cholesterol ,total bilirubin and peroxynitrite radical concentrations, while GSH concentration was a significantly decrease. PSO caused an alleviation to the hepatic dysfunction induced by sodium fluoride (group T2) manifested through significant elevation of GSH concentration, in addition, a significant reduction in serum transaminases activity, total cholesterol, peroxynitrite radical and total bilirubin concentrations. In contrast, administration of pomegranate seed oil (group T3) showed no alterations in most of these parameters. Furthermore histopathological examination of liver tissues of group T1 manifested aggregation of mononucleated cells, proliferation of hepatocyte, cytoplasmic fat droplet and granulomatous lesion consists of aggregation of macrophage and lymphocyte. All these alteration in liver histology were modified by treatment of rats with pomegranate seed oil (group T2) and no pathological lesion was reported in group T3. On conclusion, this study documented the beneficial effect of pomegranate seed oil against the deleterious effects of SF on liver functions of adult female rats.